Metal oxide powder composition, doped indium oxide target material and preparation method and application of doped indium oxide target material
By using powder compositions of indium oxide, titanium oxide, zirconium oxide and tantalum oxide to prepare doped indium oxide targets, the problems of low light transmittance and low carrier mobility in the near infrared region are solved, and a TCO film with high mobility and high light transmittance are achieved to meet the needs of the new generation of photovoltaic power generation devices.
Patent Information
- Application Number
- CN202411803525.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The existing ITO films have low light transmittance and low carrier mobility in the near-infrared region, making it difficult to meet the demand for TCO films of the new generation of photovoltaic power generation devices.
A metal oxide powder composition, including indium oxide, titanium oxide, zirconium oxide and tantalum oxide, is provided for preparing doped indium oxide targets, and a TCO film with high mobility and high light transmittance is prepared by steps such as grinding, granulation, degreasing and oxygen-rich sintering.
The high mobility and high light transmittance of TCO films are achieved, the carrier mobility is ≥75cm2/(V·s), and the average light transmittance in the 400-1200nm band is >85%, meeting the needs of the new generation of photovoltaic power generation devices.
Smart Images

Figure BDA0005178903500000081 
Figure BDA0005178903500000082 
Figure BDA0005178903500000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of target material production, and in particular relates to a metal oxide powder composition, a doped indium oxide target material, and a preparation method and application thereof. Background Art
[0002] Transparent Conductive Oxide (TCO) is a thin film material with high transmittance and low resistivity in the visible light spectrum range (380nm<λ<780nm). TCO thin film materials mainly include oxides such as CdO, In2O3, SnO2 and ZnO and their corresponding composite multi-component compound semiconductor materials. Among them, tin-doped indium oxide (Indiμm Tin Oxide, referred to as ITO) is currently the most widely used transparent conductive oxide, accounting for more than 90% of the world market share. However, ITO films have some disadvantages, such as low transmittance in the near-infrared region (60-70%), relatively low carrier mobility (30-40cm 2 / (V·s)), it is difficult to meet the demand for TCO films in the new generation of photovoltaic power generation devices. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a metal oxide powder composition, a doped indium oxide target material, and a preparation method and application thereof. The doped indium oxide target material provided by the present invention has low resistance, and the TCO film prepared therefrom has high mobility and high transmittance (>85%) in the near-infrared band.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] The invention provides a metal oxide powder composition, which comprises, by weight percentage, 95.5-99.1% of indium oxide powder, 0.3-1.5% of titanium oxide powder, 0.3-1.5% of zirconium oxide powder and 0.3-1.5% of tantalum oxide powder.
[0006] The present invention also provides a doped indium oxide target prepared by the metal oxide powder composition described in the above technical solution, which includes the following components in mass percentage: In2O3 95.5-99.1%, TiO2 0.3-1.5%, ZrO2 0.3-1.5% and Ta2O5 0.3-1.5%.
[0007] Preferably, the density of the doped indium oxide target is 7.09-7.12 g / cm 3 , volume resistivity <0.6mΩ·cm.
[0008] The present invention also provides a method for preparing the doped indium oxide target material described in the above technical solution, comprising the following steps:
[0009] Indium oxide powder, titanium oxide powder, zirconium oxide powder, tantalum oxide powder, water and a dispersant are mixed and pre-dispersed, and then ground to obtain a pre-made slurry;
[0010] The prefabricated slurry and the binder are mixed and pre-dispersed for a second time, and then granulated to obtain mixed granules;
[0011] The green body obtained by molding the mixed granular material is degreased and oxygen-enriched sintered in sequence to obtain the doped indium oxide target material.
[0012] Preferably, the degreasing is heating degreasing; the temperature of the heating degreasing is 600-800° C., and the insulation time is 2-5 hours.
[0013] Preferably, the temperature of the oxygen-enriched sintering is 1200-1450° C., the oxygen pressure is 0.05-0.1 MPa, and the insulation time is 10-25 hours.
[0014] Preferably, the molding process is cold isostatic pressing; the pressure of the cold isostatic pressing is 200-300 MPa, and the time is 5-30 min.
[0015] Preferably, the heating rate to the oxygen-enriched sintering temperature is 0.3-1° C. / min.
[0016] The present invention also provides the use of the doped indium oxide target material described in the above technical solution or the doped indium oxide target material prepared by the preparation method described in the above technical solution in the preparation of a transparent conductive oxide film.
[0017] The present invention also provides a transparent conductive oxide film, wherein the raw materials for preparing the transparent conductive oxide film include: the doped indium oxide target material described in the above technical solution or the doped indium oxide target material prepared by the preparation method described in the above technical solution; the carrier mobility of the transparent conductive oxide film is ≥75cm 2 / (V·s), the average transmittance at 400-1200nm is >85%.
[0018] The invention provides a metal oxide powder composition, which comprises, by weight percentage, 95.5-99.1% of indium oxide powder, 0.3-1.5% of titanium oxide powder, 0.3-1.5% of zirconium oxide powder and 0.3-1.5% of tantalum oxide powder.
[0019] The process of doping elements entering the indium oxide lattice will cause lattice distortion and change the lattice size and shape. The doped indium oxide target provided by the present invention has indium oxide (In2O3) as the main component (95.5-99.1wt%), and the doped TiO2, ZrO2, and Ta2O5 are tetravalent and pentavalent metal oxides. 4+The ionic radius of Zr is 0.060. 4+ The ionic radius of Ta is 0.072. 5+ The ionic radius is 0.064, which is smaller than In 3+ The ion radius of 0.08 has little effect on the crystal morphology of indium oxide, and the indium oxide crystal form remains relatively more complete. At the same time, its grain size can be refined, and the bulk resistance of the doped indium oxide target is reduced while ensuring high density; and compared with the 10wt% doping of traditional ITO (indium oxide to tin oxide 90:10), the concentration of the doping component in the doped indium oxide target provided by the present invention is reduced to less than 5wt%, so that the influence of ion impurity scattering is weakened, and the carrier mobility is improved compared with the traditional ITO, and the high mobility can reduce long-wave absorption, thereby improving the transmittance of the TCO film in the near-infrared band (>85%). DETAILED DESCRIPTION
[0020] The invention provides a metal oxide powder composition, which comprises, by weight percentage, 95.5-99.1% of indium oxide powder, 0.3-1.5% of titanium oxide powder, 0.3-1.5% of zirconium oxide powder and 0.3-1.5% of tantalum oxide powder.
[0021] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0022] As an embodiment, the metal oxide powder composition includes, by mass percentage, 96-99% indium oxide powder, 0.5-1% titanium oxide powder, 0.5-1% zirconium oxide powder and 0.5-1% tantalum oxide powder; in a specific embodiment, the metal oxide powder composition includes: 95.5% indium oxide powder, 1.5% titanium oxide powder, 1.5% zirconium oxide powder and 1.5% tantalum oxide powder, or 96.7% indium oxide powder, 1.1% titanium oxide powder, 1.1% zirconium oxide powder and 1.1% tantalum oxide powder, or 98.2% indium oxide powder, 0.6% titanium oxide powder, 0.6% zirconium oxide powder and 0.6% tantalum oxide powder, or 99.1% indium oxide powder, 0.3% titanium oxide powder, 0.3% zirconium oxide powder and 0.3% tantalum oxide powder, or 98.4% indium oxide powder, 0.6% titanium oxide powder, 0.6% zirconium oxide powder and 0.4% tantalum oxide powder.
[0023] As an embodiment, the particle sizes of the indium oxide powder, titanium oxide powder, zirconium oxide powder and tantalum oxide powder are independently ≤1 μm; the purity of the indium oxide powder, titanium oxide powder, zirconium oxide powder and tantalum oxide powder are independently ≥99.99%, and in a specific embodiment, 99.99%.
[0024] The present invention also provides a doped indium oxide target prepared by the metal oxide powder composition described in the above technical solution, which includes the following components in mass percentage: In2O3 95.5-99.1%, TiO2 0.3-1.5%, ZrO2 0.3-1.5% and Ta2O5 0.3-1.5%.
[0025] As an embodiment, the doped indium oxide target comprises the following components, in terms of mass percentage: In2O3 96-99%, TiO2 0.5-1%, ZrO2 0.5-1% and Ta2O5 0.5-1%; in a specific embodiment, the doped indium oxide target comprises the following components: In2O3 95.5%, TiO2 1.5%, ZrO2 1.5% and Ta2O5 1.5%, or In2O3 96 .7%, TiO21.1%, ZrO21.1% and Ta2O51.1%, or In2O398.2%, TiO20.6%, ZrO20.6% and Ta2O50.6%, or In2O399.1%, TiO20.3%, ZrO20.3% and Ta2O50.3%, or In2O398.4%, TiO20.6%, ZrO20.6% and Ta2O50.4%.
[0026] As an embodiment, the density of the doped indium oxide target is 7.09-7.12 g / cm 3 , relative density>99.2%, volume resistivity<0.6mΩ·cm. In a specific embodiment, the density of the doped indium oxide target is 7.094, 7.096, 7.101, 7.102, 7.107, 7.108 or 7.114 g / cm 3 , the relative density is 99.21%, 99.24%, 99.31%, 99.32%, 99.39%, 99.41% or 99.49%, and the volume resistivity is 0.46, 0.48, 0.51, 0.52, 0.54, 0.56 or 0.58 mΩ·cm.
[0027] The process of doping elements entering the indium oxide lattice will cause lattice distortion and change the lattice size and shape. However, the doped indium oxide target provided by the present invention has indium oxide (In2O3) as the main component (95.5-99.1wt%), and the doped TiO2, ZrO2, and Ta2O5 are tetravalent and pentavalent metal oxides. 4+ The ionic radius of Zr is 0.060. 4+ The ionic radius of Ta is 0.072. 5+ The ionic radius is 0.064, which is smaller than In 3+The ion radius of 0.08 has little effect on the crystal morphology of indium oxide, and the indium oxide crystal form remains relatively more complete. At the same time, its grain size can be refined, and the bulk resistance of the doped indium oxide target is reduced while ensuring high density; and compared with the 10wt% doping of traditional ITO (indium oxide to tin oxide 90:10), the concentration of the doping component in the doped indium oxide target provided by the present invention is reduced to less than 5wt%, so that the influence of ion impurity scattering is weakened, and the carrier mobility is improved compared with the traditional ITO, and the high mobility can reduce long-wave absorption, thereby improving the transmittance of the TCO film in the near-infrared band (>85%).
[0028] The present invention also provides a method for preparing the doped indium oxide target material described in the above technical solution, comprising the following steps:
[0029] Indium oxide powder, titanium oxide powder, zirconium oxide powder, tantalum oxide powder, water and a dispersant are mixed and pre-dispersed, and then ground to obtain a pre-made slurry;
[0030] The prefabricated slurry and the binder are mixed and pre-dispersed for a second time, and then granulated to obtain mixed granules;
[0031] The green body obtained by molding the mixed granular material is degreased and oxygen-enriched sintered in sequence to obtain the doped indium oxide target material.
[0032] The invention prepares a prefabricated slurry by mixing indium oxide powder, titanium oxide powder, zirconium oxide powder, tantalum oxide powder, water and a dispersant for first pre-dispersion and then grinding the mixture.
[0033] As an embodiment, the dispersant is polyvinyl pyrrolidone; the mass of the dispersant is 0.5-1.5% of the total mass of the indium oxide powder, titanium oxide powder, zirconium oxide powder and tantalum oxide powder, and is 1% in a specific embodiment; the water is pure water; the mass of the water is 8-120% of the total mass of the indium oxide powder, titanium oxide powder, zirconium oxide powder and tantalum oxide powder, and is 90% in a specific embodiment.
[0034] As an implementation mode, indium oxide powder, titanium oxide powder, zirconium oxide powder, tantalum oxide powder, water and a dispersant are mixed as follows: water, a dispersant, indium oxide powder, titanium oxide powder, zirconium oxide powder and tantalum oxide powder are sequentially added into a mixing container; the mixing container is a mixing barrel.
[0035] As an embodiment, the first pre-dispersion time is 5 to 15 minutes, and in a specific embodiment, it is 10 minutes.
[0036] As an implementation mode, the grinding is ball milling or sand milling, and in a specific embodiment, it is sand milling; the time of the ball milling is ≥ 24 hours, and in a specific embodiment, it is 24 hours; the speed of the sand milling is 2100 r / min; the time of the sand milling is 1 to 5 hours, and in a specific embodiment, it is 3 hours. The present invention has no special limitation on the speed of the ball milling, and any speed known in the art can be used.
[0037] As an embodiment, the particle size of the mixed powder obtained by grinding is D 50 <0.25μm, in a specific embodiment D 50 =0.21μm.
[0038] After obtaining the prefabricated slurry, the present invention mixes the prefabricated slurry and a binder for a second pre-dispersion, and then granulates to obtain mixed granules.
[0039] As an embodiment, the binder is polyvinyl alcohol (PVA) and polyethylene glycol (PEG); the mass of the polyvinyl alcohol is 0.5-1.5% of the total mass of the indium oxide powder, titanium oxide powder, zirconium oxide powder and tantalum oxide powder, and in a specific embodiment it is 1%; the mass of the polyethylene glycol is 1-2% of the total mass of the indium oxide powder, titanium oxide powder, zirconium oxide powder and tantalum oxide powder, and in a specific embodiment it is 1.5%.
[0040] As an embodiment, the second pre-dispersion time is 5 to 15 minutes, and in a specific embodiment is 10 minutes.
[0041] As an embodiment, the granulation is spray drying granulation; the outlet air temperature of the spray drying granulation is 95-110°C, and in a specific embodiment it is 100°C, and the inlet air temperature is 220-245°C, and in a specific embodiment it is 220°C.
[0042] As an embodiment, the equipment used for granulation is a centrifugal spray drying tower.
[0043] As an embodiment, the particle size of the mixed granules obtained by granulation is 30 to 50 μm, and in a specific embodiment, it is 50 μm.
[0044] After obtaining the mixed granular material, the present invention subjects the mixed granular material to a molding process to obtain a green body.
[0045] As an implementation mode, before the molding process, the present invention mixes and sieves the mixed granules to obtain powder.
[0046] As an implementation mode, the equipment used for mixing is a mixer; the equipment used for screening is a screening machine; the aperture of the sieve used for screening is 60 to 100 meshes, and in a specific embodiment is 80 meshes.
[0047] As an embodiment, the forming process is cold isostatic pressing; the pressure of the cold isostatic pressing is 200-300 MPa, the time is 5-30 min, and the density of the green body is 55-65%. As another embodiment, the pressure of the cold isostatic pressing is 200-250 MPa, 250 MPa in a specific embodiment, the time is 10-20 min, 15 min in a specific embodiment, and the density of the green body is 61%.
[0048] As an embodiment, the equipment used for the cold isostatic pressing is a cold isostatic press.
[0049] The invention presses the powder into a block with a certain shape through cold isostatic pressing.
[0050] After obtaining the green body, the present invention degreases the green body to obtain a degreased green body.
[0051] As an embodiment, the degreasing is heating degreasing; the temperature of the heating degreasing is 600-800°C, and the holding time is 2-5 hours; the degreasing is carried out in air. As another embodiment, the temperature of the heating degreasing is 650-750°C, and in a specific embodiment, it is 650°C, and the holding time is 3-5 hours, and in a specific embodiment, it is 4 hours.
[0052] As an implementation manner, the heating rate to the heating degreasing temperature is 1-2°C / min, and in a specific embodiment is 1.5°C / min.
[0053] The present invention volatilizes the dispersant and binder added in the grinding process by heating and degreasing, so as to avoid affecting the subsequent sintering.
[0054] After obtaining the degreased green body, the present invention performs oxygen-enriched sintering on the degreased green body to obtain a doped indium oxide target.
[0055] As an embodiment, the temperature of the oxygen-enriched sintering is 1200-1450°C, the oxygen pressure is 0.05-0.1MPa, and the holding time is 10-25h. As another embodiment, the temperature of the oxygen-enriched sintering is 1300-1450°C, 1200°C, 1300°C or 1450°C in specific embodiments, the oxygen pressure is 0.08-0.1MPa, 0.08MPa or 0.1MPa in specific embodiments, and the holding time is 15-25h, 15h or 25h in specific embodiments. The oxygen-enriched sintering of the present invention is to increase the oxygen partial pressure of the sintering environment to inhibit the decomposition of the oxide raw material at high temperature, thereby increasing the density of the target material.
[0056] As an implementation manner, the heating rate to the temperature of oxygen-enriched sintering is 0.3-1°C / min, and in a specific embodiment is 0.8°C / min.
[0057] As an implementation mode, after the oxygen-enriched sintering, the present invention naturally cools the product obtained by the oxygen-enriched sintering to room temperature to obtain a doped indium oxide target.
[0058] The present invention can improve the sintering density through oxygen-enriched sintering. Within the above heating rate, it can avoid the problem of too fast shrinkage due to too fast heating, which leads to cracking of the sintered product, and it can also avoid the problem of extending the time of the entire sintering process due to too slow heating, which easily leads to grain growth and equipment waste. Within the above insulation time, it can avoid the problem of non-density of the target material due to short insulation time, and it can also avoid the problem of grain growth due to too long insulation time, or overburning leading to density reduction.
[0059] The present invention also provides the use of the doped indium oxide target material described in the above technical solution or the doped indium oxide target material prepared by the preparation method described in the above technical solution in the preparation of a transparent conductive oxide film.
[0060] The present invention also provides a transparent conductive oxide film, wherein the raw materials for preparing the transparent conductive oxide film include: the doped indium oxide target material described in the above technical solution or the doped indium oxide target material prepared by the preparation method described in the above technical solution; the carrier mobility of the transparent conductive oxide film is ≥75cm 2 / (V·s), the average transmittance at 400-1200 nm is >85%, and in the specific embodiment >88%.
[0061] In a specific embodiment, the carrier mobility of the transparent conductive oxide film is 75, 76, 78, 79, 81 or 84 cm 2 / (V·s).
[0062] In a specific embodiment, the average light transmittance of the transparent conductive oxide film at 400-1200 nm is 88.2%, 88.7%, 89.1%, 89.3%, 89.4%, 89.8% or 90.4%.
[0063] As an embodiment, the method for preparing the transparent conductive oxide film is: preparing a transparent conductive oxide film (TCO film) by sputtering the doped indium oxide target.
[0064] As an embodiment, the sputtering coating is physical vapor deposition (PVD) sputtering coating; the power of the sputtering coating is 120-200W, and in a specific embodiment it is 150W; the atmosphere of the sputtering coating is a mixed gas comprising argon, oxygen and hydrogen, the volume fraction of oxygen in the mixed gas is 0.1-1.5%, the volume fraction of hydrogen is 0.1-3%, and the rest is argon, in a specific embodiment the volume fraction of oxygen is 1%, the volume fraction of hydrogen is 1.8%, and the rest is argon; the thickness of the transparent conductive oxide film is 80-120nm, and in a specific embodiment it is 100nm.
[0065] The technical solutions of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0066] Example 1
[0067] Indium oxide powder, titanium oxide powder, zirconium oxide powder and tantalum oxide powder were weighed according to the mass percentage of 95.5%, 1.5%, 1.5% and 1.5% respectively. The particle size of the powders was ≤1μm and the purity was 99.99%. Pure water, polyvinyl pyrrolidone, indium oxide powder, titanium oxide powder, zirconium oxide powder and tantalum oxide powder were added to the mixing barrel in turn. The powders were pre-dispersed for 10 minutes. The mass of polyvinyl pyrrolidone accounted for 1% of the total mass of indium oxide powder, titanium oxide powder, zirconium oxide powder and tantalum oxide powder; the mass of pure water accounted for 90% of the total mass of indium oxide powder, titanium oxide powder, zirconium oxide powder and tantalum oxide powder. The pre-dispersed slurry was pumped into a sand mill and ground at 2100r / min for 3h. The D 50 =0.21 μm, and a prefabricated slurry is obtained;
[0068] Adding binders polyvinyl alcohol (PVA) and polyethylene glycol (PEG) to the obtained prefabricated slurry in sequence, pre-dispersing for 10 minutes, wherein the mass of PVA and PEG is 1% and 1.5% of the total mass of indium oxide powder, titanium oxide powder, zirconium oxide powder and tantalum oxide powder, respectively, to obtain a mixed slurry;
[0069] The mixed slurry is put into a centrifugal spray drying tower for spray drying and granulation, the inlet air temperature of the spray drying and granulation is 220°C, the outlet air temperature is 100°C, the particle size of the obtained mixed granules is 50 μm, the obtained powder is mixed with a mixer, and then sieved with a sieving machine, wherein the sieve is 80 mesh;
[0070] The prepared mixed pellets were pressed in a cold isostatic press at 250 MPa for 15 min to obtain a green body with a density of 61%;
[0071] The green body is placed in a sintering furnace, first heated to 650°C at a heating rate of 1.5°C / min, heated and degreased in air for 4 hours, then heated to 1200°C at a heating rate of 0.8°C / min, with an oxygen pressure of 0.1MPa, and oxygen-enriched sintering is performed for 25 hours, and then naturally cooled to room temperature to obtain a doped indium oxide target;
[0072] The doped indium oxide target is sputtered by physical vapor deposition (PVD) to obtain a transparent conductive oxide film (TCO film), the sputtering power is 150 W, the sputtering atmosphere is a mixed gas containing argon, oxygen and hydrogen, wherein the volume fraction of oxygen is 1%, the volume fraction of hydrogen is 1.8%, and the rest is argon, and the thickness of the obtained transparent conductive oxide film is 100 nm.
[0073] The density of the doped indium oxide target was 7.114 g / cm 3 , relative density is 99.49%, volume resistivity is 0.54mΩ·cm, and the mobility of 100nm thick TCO film prepared by this target is 78cm 2 / (V·s), the average transmittance in the 400-1200nm band is 89.8%.
[0074] Examples 2 to 7 and Comparative Examples 1 to 5
[0075] The differences in process parameters and component contents of each embodiment and comparative example from those of embodiment 1 are shown in Table 1.
[0076] Table 1 Process parameters and component contents of each embodiment and comparative example
[0077]
[0078] Performance Testing
[0079] The performance test results of the doped indium oxide targets prepared in the embodiments and comparative examples, and the TCO films prepared therefrom are shown in Table 2.
[0080] Table 2 Performance test results of various embodiments and comparative examples
[0081]
[0082]
[0083] As can be seen from Table 2, by comparing Examples 1 to 7 with Comparative Examples 1 to 5, it can be found that titanium oxide, zirconium oxide and tantalum oxide, at specific addition amounts, can obtain a doped indium oxide target with high density, low bulk resistance, high carrier mobility and high transmittance, while when only two of the three components of titanium oxide, zirconium oxide and tantalum oxide are added, the density of the obtained doped indium oxide target is significantly reduced, the bulk resistance is significantly increased, and the carrier mobility and transmittance do not meet the expected requirements.
[0084] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A metal oxide powder composition, characterized in that Calculated by mass percentage, it includes: 95.5-99.1% of indium oxide powder, 0.3-1.5% of titanium oxide powder, 0.3-1.5% of zirconium oxide powder and 0.3-1.5% of tantalum oxide powder.
2. A doped indium oxide target prepared using the metal oxide powder composition according to claim 1, characterized in that: Calculated by mass percentage, it includes the following components: In2O3 95.5-99.1%, TiO2 0.3-1.5%, ZrO2 0.3-1.5% and Ta2O5 0.3-1.5%.
3. The doped indium oxide target according to claim 2, characterized in that: The density of the doped indium oxide target is 7.09-7.12 g / cm 3 , volume resistivity <0.6mΩ·cm.
4. The method for preparing the doped indium oxide target according to claim 2 or 3, characterized in that: The following steps are involved: Indium oxide powder, titanium oxide powder, zirconium oxide powder, tantalum oxide powder, water and a dispersant are mixed and pre-dispersed, and then ground to obtain a pre-made slurry; The prefabricated slurry and the binder are mixed and pre-dispersed for a second time, and then granulated to obtain mixed granules; The green body obtained by molding the mixed granular material is degreased and oxygen-enriched sintered in sequence to obtain the doped indium oxide target material.
5. The preparation method according to claim 4, characterized in that: The degreasing is performed by heating; the temperature of the heating degreasing is 600-800° C., and the heat preservation time is 2-5 hours.
6. The preparation method according to claim 4, characterized in that: The temperature of the oxygen-enriched sintering is 1200-1450° C., the oxygen pressure is 0.05-0.1 MPa, and the insulation time is 10-25 hours.
7. The preparation method according to claim 4, characterized in that: The molding process is cold isostatic pressing; the pressure of the cold isostatic pressing is 200-300 MPa and the time is 5-30 minutes.
8. The preparation method according to claim 4 or 6, characterized in that: The heating rate to the temperature of the oxygen-enriched sintering is 0.3-1°C / min.
9. Use of the doped indium oxide target material according to claim 2 or 3 or the doped indium oxide target material prepared by the preparation method according to any one of claims 4 to 8 in the preparation of a transparent conductive oxide film.
10. A transparent conductive oxide film, characterized in that: The raw materials for preparing the transparent conductive oxide film include: the doped indium oxide target material according to claim 2 or 3 or the doped indium oxide target material prepared by the preparation method according to any one of claims 4 to 8; the carrier mobility of the transparent conductive oxide film is ≥75cm 2 / (V·s), the average transmittance at 400-1200nm is >85%.
Citation Information
Cited By
Vacuum evaporation coating method, evaporation source material and preparation method of evaporation source material
CN120423875A